2012
DOI: 10.1007/s10548-012-0233-2
|View full text |Cite
|
Sign up to set email alerts
|

My Voice or Yours? An Electrophysiological Study

Abstract: This study examined the neural processes underlying own voice discrimination using electrophysiological methods. Event-related potentials were recorded while healthy subjects (n = 17) heard passively three oddball sequences composed of recordings of the French vowel/a/pronounced either by the participant her/himself or by two unknown persons. The results indicated that, although the mismatch negativity (MMN) displayed similar peak latency and amplitude in both conditions, the subsequent P3a clearly distinguish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
71
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(78 citation statements)
references
References 69 publications
6
71
1
Order By: Relevance
“…The authors reported no differences in the mismatch negativity (MMN) responses to self-generated versus nonself voice stimuli (Graux et al, 2015;Graux et al, 2013). However, the authors observed a reduced reorienting response to one's own voice, in comparison with both unknown (Graux et al, 2013) and familiar (Graux et al, 2015) voice stimuli, reflected by smaller P3a amplitudes to the self-generated voice. These findings were interpreted as evidence for the prioritized processing of nonself voice stimuli when compared with a self-generated voice, in a context in which individuals' attention was engaged in a concurrent visual task.…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…The authors reported no differences in the mismatch negativity (MMN) responses to self-generated versus nonself voice stimuli (Graux et al, 2015;Graux et al, 2013). However, the authors observed a reduced reorienting response to one's own voice, in comparison with both unknown (Graux et al, 2013) and familiar (Graux et al, 2015) voice stimuli, reflected by smaller P3a amplitudes to the self-generated voice. These findings were interpreted as evidence for the prioritized processing of nonself voice stimuli when compared with a self-generated voice, in a context in which individuals' attention was engaged in a concurrent visual task.…”
mentioning
confidence: 92%
“…An important contribution to the comprehension of the neurocognitive correlates of self-generated voice processing in later information-processing stages comes from two recent ERP studies investigating both the preattentive deviance detection and the orienting response to one's own versus a nonself voice (Graux, Gomot, Roux, Bonnet-Brilhault, & Bruneau, 2015;Graux et al, 2013). In these experiments, participants were asked to pay attention to a silent movie and to ignore the concurrent acoustic stimulation, consisting of recordings of their own voices, as well as voices from unknown (Graux et al, 2013) and familiar (Graux et al, 2015) speakers.…”
mentioning
confidence: 99%
See 3 more Smart Citations